CFD modeling and simulation of PEM fuel cell using OpenFOAM - Kone, Jean-Paul; Zhang, Xinyu; Yan, Yuying; Hu, Guilin; Ahmadi, Goodarz (Elsevier, 2018)
A proton exchange membrane (PEM) fuel cell is an electrolytic cell that converts chemical energy of hydrogen reacting with oxygen into electrical energy. To meet increasingly stringent application needs, improved performance and increased efficiency are paramount. Computational fluid dynamics (CFD) is an ideal means for achieving these improvements. In this paper, a comprehensive CFD-based tool that can accurately simulate the major transport phenomena which take place within a PEM fuel cell is presented. The tool is developed using OpenFOAM and it can be used to rapidly gain insights into the cell working processes. The base case results are compared with previous model results and experimental data. The present I-V curve shows better agreement with the experimental trend at low current densities. The simulation data also indicate that the chosen concentration constant has very significant impact on the concentration overpotential.